IDENTIFIKASI FUNGI PADA TAPE BERAS MERAH (ORYZA SATIVA GLABERRIMA) SERTA PERANANNYA SEBAGAI SUMBER BELAJAR BERUPA MODUL TERHADAP KETERAMPILAN MERENCANAKAN PERCOBAAN PADA POKOK BAHASAN FUNGI SISWA KELAS X SMA - Setyowati, Nining; Harlita, Harlita; Muzayyinah, Muzayyinah (Pendidikan Biologi, 2011)
ABSTRACT - The purpose of this study was to (1) Identify the type of fungus found on red rice tape (Oryza sativa glabberima). (2) Determine differences in students the skills  to plan  experiments  in  teaching and learning process  with additional learning resources  in the form of modules  results  in  the learning process without additional module on research results of class X SMA Al Islam 1 Surakarta. This study population is the entire class X SMA Al Islam 1 Surakarta odd semester of the academic year 2011/2012. The sample in this study were students in class X-7  as a  control class  and the  class X-8  as a  class  experiment. Cluster sampling technique with Random Sampling. The results of biological research in the form of  modules  as  independent variables and  students'  skills  to plan  the experiment as the dependent variable. Data collection techniques of  the skills  to plan an experiment using the documentation and observation sheet. Techniques of data analysis using  t test.  This study is a  quasi-experimental studies  (Quasi Experiment) using Randomized Control Design Only. The results of  this study summed up as  follows:  (1) Fungi  in  the red  rice tape  involved in  rice  fermentation  process  found  two  genera  of  Saccharomyces and Aspergillus viewed from morphological features. (2) There are differences in students  the skills  to plan  experiments  in  teaching and learning process  with additional  learning resources  in the form of  modules  results  in  the learning process without additional module on research results of class X SMA Al Islam 1 Surakarta.   Keywords: The Identification of Fungi, Skill For Planning A Research